ANALISIS KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA SMA DALAM MENYELESAIKAN SOAL BERTIPE HIGHER ORDER THINKING SKILLS (HOTS) - Aisyah, Nurul (OMEGA: Jurnal Keilmuan Pendidikan Matematika, 2025)
This study aims to describe the concept understanding ability of high school students in solving HOTS-type problems in high, medium, and low categories and to find out students’ responses in solving issues on SPLTV material. This research is qualitative research with a descriptive method. The technique of taking subjects by purposive sampling. Taking the subject of class X IPA / IPS SMAIT, Nurul Fajri as many as 3 students out of 19 students. Data collection techniques using HOTS- type mathematical concept understanding ability description test, interviews, and documentation. Based on the results of the study, it shows that the achievement of indicators of the ability to understand mathematical concepts in solving HOTS- type problems includes: 1) Subject NF-17 high ability indicators restate concepts that have been learned, questions 1, 2, and 4. Indicators classify objects based on concepts, apply concepts algorithmically, relate various mathematical concepts internally or externally, provide examples or counter examples, and present concepts in various representations of questions 1, 3, and 4. 2) Subject NF-18 medium ability indicator restates the concepts that have been learnt, question 4. Indicators classify objects based on concepts, apply concepts algorithmically, and relate various mathematical concepts internally or externally, questions 1 and 4. Indicators provide examples or counterexamples of question 1. 3) Subject NF-10 low ability indicator restates the concepts that have been learnt in question 1.